Self-poisoning suicides in England: a multicentre study. - Kapur, N; Turnbull, P; Hawton, K; Simkin, S; Sutton, L; Mackway-Jones, K; Bennewith, O; Gunnell, D (2005)
BACKGROUND: Suicide by self-poisoning is an important cause of death worldwide. A substantial proportion of those with a fatal outcome may come into contact with medical services before they die. AIM: To estimate the proportion of self-poisoning suicides who reached hospital alive; to compare those who reached hospital alive with those who did not; to describe in detail the clinical characteristics and medical management of those dying in hospital. DESIGN: Retrospective audit. METHODS: We studied 24 coroners' jurisdictions across England, reviewing coroners' files and identifying all suicides by self-poisoning (drugs and other ingestible poisons) from 1 January 2001 to 31 December 2001. RESULTS: Of the 214 individuals who completed suicide by self-poisoning during the study period, 49 (23%) reached hospital alive. Those reaching hospital were more likely to be female, more likely to have ingested paracetamol and less likely to have ingested co-proxamol. In the hospital sample, the commonest causes of death were respiratory (n = 10), hepatic or hepatorenal (n = 8), cardiac (n = 5), or a result of hypoxic brain injury (n = 5). Only 18% of in-hospital deaths occurred within 24 h of the overdose. DISCUSSION: Extrapolating to England as a whole, we might expect 300 self-poisoning suicides per year to reach hospital alive (6% of all suicides). Improved medical management might produce a small but significant reduction in the rate of suicide. Such interventions should not be restricted to the emergency care domain. Further research will help to clarify the likely contribution of improved medical management to suicide prevention.